HUBUNGAN ANTARA KEPERCAYAAN DIRI DENGAN KOMUNIKASI INTERPERSONAL SISWA KELAS XI SMK - Tesa Febri Veolina; Umbu Tagela; Yustinus Windrawanto (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
Self-confidence influences the way a person interacts and communicates with other people. Confident people tend to build stronger relationships because they can express themselves without worrying about being rejected or criticized. Conversely, a lack of self-confidence can prevent a person from building healthy and mutually beneficial relationships. This research aims to determine the relationship between self-confidence and interpersonal communication in class XI students. This research is quantitative research with 67 class XI vocational school students as research subjects. The sampling technique used was total sampling. Data collection in this study used a scale of self-confidence and interpersonal communication. The research data was analyzed using Kendall's Tau-b correlation with the help of an application IBM SPSS Statistic 23.0. The results of data analysis show that there is a relationship between self-confidence and interpersonal communication as evidenced by the obtained r value = 420 and p value = 0.000.